ChatGPT's Role in Transforming Employee Recruitment and Selection Processes - Itot Bian Raharjo (Institut Riset dan Publikasi Indonesia, 2023)
Employee recruitment and selection is a key process in human resource management that plays an important role in the success of an organisation. This process involves the search, evaluation and selection of individuals who have the qualifications and potential that match the needs of the organisation. One of the significant changes that has transformed the employee recruitment and selection paradigm is the advent of advanced technologies such as ChatGPT. This research aims to analyse the role of ChatGPT in the transformation of the employee recruitment and selection process. The method used is a qualitative literature review that focuses on an in-depth understanding of the topic in the time span from 2018 to 2023. The main objective of this method is to identify, analyse, and synthesise relevant scientific literature that has been published in various journals, conference papers, and other academic sources accessible through Google Scholar. The study results show that the use of ChatGPT in the transformation of employee recruitment and selection processes is a significant step towards higher efficiency and effectiveness in human resource management. However, we must remain cautious in the face of emerging impacts and challenges.